Curriculum mapping food science programs: An approach to quantification of professional competencies. Issue 2 (13th March 2020) - Weston, Emma; Benlloch‐Tinoco, Maria; Mossop, Liz; McCullough, Fiona; Foster, Tim
Abstract: It is fundamental that students are able to identity where they have developed specific professional competencies during their study. This ensures students can not only articulate their competencies well in job applications and assessments but also draw on their experiences for use in the workplace. The aim of study was to ascertain if desirability of an element or competency as indicated by employers, was reflected in an equivalent level of program content, appropriately perceived by the student. A case study approach mapped elements of the previously developed Competencies for Food Graduate Careers framework against food sciences curricula at University of Nottingham. The mapping process facilitated evaluation of appropriate levels of inclusion of each element in degree programs, by recording types of content and experiences provided, in collaboration with teaching staff. Perspectives of the student experience were captured using an online survey. In addition, guidance from a prior industry survey provided context of the level of desirability for each element across the range of graduate roles in the United Kingdom. The results showed some areas of mismatch, where curricular content did not align with employer expectations or student perceptions. This has informed review of this curriculum, to best reflect "competency development" to meet the needs of the food industry. Recommendations were made to address gaps through enhancement of content, delivery, communication, or assessment. Additionally, the exercise has suggested a more informed development of curricula categorization and coding for future similar mapping activities.